Clinical failure analysis of contemporary ceramic-on-ceramic total hip replacements. (August 2013) - Brandt, Jan-M; Gascoyne, Trevor C; Guenther, Leah E; Allen, Andrew; Hedden, David R; Turgeon, Thomas R; Bohm, Eric R
The present study investigates the performance of ceramic-on-ceramic total hip replacements by combining a retrieval analysis with a survivorship analysis to elucidate mechanisms that led to clinical failure. Semiquantitative surface damage assessment, contact profilometry, contour measurements, and scanning electron microscopy were performed to characterize the types and quantify the extent of surface damage on the retrieved ceramic components. The implantation period was positively correlated with both damage scores of the femoral heads (R = 0.573, p < 0.001) and the acetabular cups (R = 0.592, p < 0.001). Increased maximal out-of-roundness values of the femoral heads correlated with both increased metal transfer damage score (R = 0.384, p  = 0.023) and increased stripe damage score (R = 0.729, p ≤ 0.001) of the acetabular liners. The damage rate (damage score/year) for both the retrieved heads and acetabular liners was at least 2.2-fold greater at inclination angles of >45° than the damage rate at inclination angles of ≤45°. For the retrieved femoral heads only, the linear wear rate of 25.5 ± 21.3 µm/year at inclination angles of >45° was 6-fold greater than the linear wear rate of 4.2 ± 2.3 µm/year at inclination angles of ≤45°. Metal transfer on the ceramic bearing surface could possibly contribute to fluid-film starvation and, in combination with an increased inclination angle, may facilitate an adhesive wear mechanism associated with stripe surface damage. At our institution, the clinical survivorship of ceramic-on-ceramic total hip replacements was 98.9% (a total of 9 out of 815 patients were revised within 10 years after total hip arthroplasty) with revision as the end point, suggesting their safe use in younger patients.